Praktik Strategi Penghematan Biaya dan Dampaknya terhadap Kinerja Sumber Daya Manusia : Perspektif Pegawai Kontrak di BPKPD Kabupaten Buleleng - Putu Ventha Agustha; Komang Krisna Heryanda; M.Rudi Irwansyah (Faculty of Economics and Business, Universitas Warmadewa, 2026)
Abstract This study aims to understand the implementation of cost-saving strategies at the Regional Finance and Revenue Management Agency (BPKPD) of Buleleng Regency and how such strategies are perceived by contract employees in relation to their performance. In the context of government budget efficiency, contract workers are often assumed to be the most affected group. Using a descriptive qualitative approach, the study employed in-depth interviews with several contract employees who had experienced the budget-saving measures directly. The findings reveal that although there were cost-saving measures such as benefit reduction and limited overtime, these did not significantly affect the performance of contract employees. Many maintained their performance standards due to strong work commitment, a sense of responsibility, and the expectation of contract renewal. These findings highlight the importance of psychological and motivational factors in maintaining performance, even in financially constrained environments. Keywords: cost-saving strategy, employee performance, contract workers, human resource management, BPKPD